(untitled) (Teología, 2020)
Based on Juan Carlos Scannone’s reading of Pope Francis’ social magisterium, I will conclude that mercy is the popular political form assumed by the community organi- zed by rights. As the fight against injustice is constitutive of evangelization, the popular movements that promote it are a sign of the times, and their discernment about ac- ting for the just transition, according to the sensus fidelium, is situated theological ethics.